2007
DOI: 10.1038/nsmb1274
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of the Dam1 kinetochore ring complex and implications for microtubule-driven assembly and force-coupling mechanisms

Abstract: The Dam1 kinetochore complex is essential for chromosome segregation in budding yeast. This ten-protein complex self-assembles around microtubules, forming ring-like structures that move with depolymerizing microtubule ends, a mechanism with implications for cellular function. Here we used EM-based single-particle and helical analyses to define the architecture of the Dam1 complex at 30-A resolution and the self-assembly mechanism. Ring oligomerization seems to be facilitated by a conformational change upon bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
148
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(162 citation statements)
references
References 33 publications
12
148
2
Order By: Relevance
“…The diameter of the ring is 50 nm and appears to interact with microtubules through electrostatic interactions via "arms" that extend from the Dam1 complex (Miranda et al 2005;Westermann et al 2005). These interactions are at least partly mediated through the N terminus of Dam1 and possibly the Duo1 subunit, which also exhibits microtubule-binding activity (Hofmann et al 1998;Cheeseman et al 2001b;Wang et al 2007;Ramey et al 2011). Although there are no atomic structures for any Dam1 components, cryo-EM analyses indicate that the complex does not appear to undergo major rearrangements upon forming a ring around the microtubule (Ramey et al 2011).…”
Section: Kmnmentioning
confidence: 99%
See 2 more Smart Citations
“…The diameter of the ring is 50 nm and appears to interact with microtubules through electrostatic interactions via "arms" that extend from the Dam1 complex (Miranda et al 2005;Westermann et al 2005). These interactions are at least partly mediated through the N terminus of Dam1 and possibly the Duo1 subunit, which also exhibits microtubule-binding activity (Hofmann et al 1998;Cheeseman et al 2001b;Wang et al 2007;Ramey et al 2011). Although there are no atomic structures for any Dam1 components, cryo-EM analyses indicate that the complex does not appear to undergo major rearrangements upon forming a ring around the microtubule (Ramey et al 2011).…”
Section: Kmnmentioning
confidence: 99%
“…(Miranda et al 2005). Each protein is present at a single copy per complex and 16 complexes can assemble into a ring around microtubules in vitro in either orientation relative to the plus end (Miranda et al 2005;Westermann et al 2005;Wang et al 2007;Ramey et al 2011). However, small oligomers and other larger Dam1 structures can also attach to microtubules, making it unclear which structures are relevant to activity in vivo (Gestaut et al 2008;Grishchuk et al 2008b).…”
Section: Kmnmentioning
confidence: 99%
See 1 more Smart Citation
“…Biochemical reconstitution revealed that about 16 Dam1 complexes oligomerize and form a ring that encircles a microtubule ( Fig. 2b; Miranda et al 2005;Westermann et al 2005;Wang et al 2007). Separate studies suggest that the Dam1 complex can also be present on a microtubule without (Miranda et al 2005;Westermann et al 2005;Wang et al 2007) but also as an oligomer that does not form a ring (Gestaut et al 2008;Grishchuk et al 2008).…”
Section: Interface Of Kinetochore Microtubule Interaction: the Ndc80 mentioning
confidence: 99%
“…Functioning as a heterodecamer with 1:1 stoichiometry (3), its distinct biophysical properties render it an attractive candidate as the coupler (4)(5)(6)(7)(8)(9)(10). In vitro, budding yeast Dam1 (ScDam1) is able to oligomerize, forming a 16-fold-symmetry ring (4, 7, 9) (25-fold by another study; ref.…”
mentioning
confidence: 99%